Flight Mill Experiments and Computer Simulations Indicate Islands Recruit More Capable Flyers of Moths - Zheng, Yu-xuan; Wang, Ying; Dai, Bo-ya; Li, Zheng; Huo, Qi-run; Cui, Jian-xin; Liu, Hao; Li, Xin-hai; Hughes, Alice C.; Zhang, Ai-bing (Frontiers in Ecology and Evolution, 2021)
Understanding the traits related to species colonization and invasion, is a key question for both pest management and evolution. One of the key components is flight, which has been measured for a number of insect species through radar and tethered flight mill systems, but a general understanding of insect flight at a community level is lacking. In this study, we used flight mill experiments to quantify flight abilities of moth species, and simulation experiments to study which moths in mainland China have the potential for cross-island dispersal. We found that moths from superfamily Geometroidea (family Geometridae) have the weakest flight ability among the seven Lepidoptera superfamilies, which is characterized by the shortest longest single flight (LSF), the shortest time corresponding to the longest single flight (TLSF) (timecorrespondingtothelongestsingleflight), the lowest total distance flown (TDF), and the lowest average speed during the flight (VTDF). Surprisingly, the family Pyralidae (superfamily Pyraloidea) has the highest flight endurance of all 186 species of 12 families in this study, which is unexpected, given its small size and morphological traits yet it shows the longest LSF and TLSF. The comparison between species common to mainland and islands shows that flight distance (LSF) may be more important for species spread than flight speed. The results of mainland-island simulations show that when P(LSF>CD) (the proportion of individuals whose LSF is greater than the closest distance (CD) between mainland and island to the total number of individuals in the population) is less than 0.004, it is difficult for moth species to disperse to across islands without relying on external factors such as airflow. Over extended periods, with the immigration of species with strong flight abilities, islands are more likely to recruit species with stronger flight abilities.